Perancangan Absensi Dosen Berbasis IoT Memanfaatkan Rfid - Harahap, Tri Martati; Riza, Ferdy (Al-DYAS, 2025)
Attendance is an important element in the lecture system, but it is usually still done manually using attendance books and lists. This manual method is often inefficient in monitoring teacher discipline in terms of attendance and return time. To solve this problem, technologies such as Internet of Things (IoT) and radio frequency identification (RFID) offer a more efficient and accurate solution. IoT allows physical objects to connect to the internet for data exchange, and RFID can be used for automatic identification. This research aims to design an IoT-based lecturer attendance system using RFID and first-in-first-out (FIFO) algorithms. This system is expected to improve the accuracy and efficiency of the instructor attendance process and replace the existing manual method.